Insights from a decade of using the Motus network to track boreal bird species from Observatoire d’oiseaux de Tadoussac, Québec to temperate and tropical wintering grounds - Jacob Walker; Jean-François Therrien; Camille Bégin-Marchand; Pascal Côté; Alexandre Terrigeol; François Gagnon; Junior A. Tremblay (Journal of Field Ornithology)
Migration is the least-studied phase of the life cycle for many bird species, despite its importance to the full understanding of their life history traits and conservation. Between 2014 and 2023, we deployed tracking devices at Observatoire d’oiseaux de Tadoussac, Québec and used the Motus Wildlife Tracking System to investigate migration patterns of 10 species that breed in boreal and Arctic habitats of eastern Canada, and migrate to wintering areas in the United States and South America. Several species were of special conservation concern in the United States and Canada. Motus receiving stations from Québec to Colombia provided migratory movements for over 350 individual birds. We present and discuss tracking duration and distances, migration routes, stopover, flight statistics, and phenology of fall migration for these species. The array of Motus receivers in the region surrounding the tagging site detected many individuals clearly upon departure, allowing for comparisons of post-capture stopover duration and departure strategy. All tagged species stopped over at the tagging location following capture (mean 8.2 days ± 6.7 SD), which could have been an effect of the capture and tagging process. Short distance migrants (mean 10.6 days ± 7.6 SD) stopped over longer than long-distance migrants (mean 5.3 days ± 3.8 SD). Prolonged (> 7 days) stopovers were detected elsewhere along the migratory routes for six of the species tagged. Eight species were detected during long-distance (> 100 km) migratory flights and estimated flight speeds were similar across species (mean 53.5 km/h ± 22.3 SD). All but one species made primarily nocturnal departures for migratory flights, and three of the species with nocturnal departures were previously thought to be diurnal migrants. The Motus network allowed a reliable method to assess and compare migratory routes and timing for a variety of small birds nesting in Arctic and boreal ecosystems.